Upaya Perawatan Morning Sickness Pada Ibu Hamil Trimester I - Siwi, Palupi Oktaviani Resti, Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep (2017)
Background : Pregnancy is a continuous process chain isting of ovulation and release of egg cells, migration of rmatozoa and ovum, conception, and the growth of the zygote, nidasi (implantation) to the uterus, placenta formation, and elopment of products of conception until atterm (Manuaba, 2010). According to research Bai (2016), 5079 women in early pregnancy, especially in the first trimester in Rotterdam area, Netherlands. In this study 33,6% of women experience nausea in early pregnancy, 9,6% experienced nausea and vomiting in early pregnancy, and to 44,4 % experienced fatigue. Objective : to deal with morning sickness in the first trimester pregnant women in accordance with the standards of nursing care. Methods : The method used in Ny. D is a case study approach, with namely by do nursing care at the start of the assessment , intervention , plementation and evaluation. Result : After 3 days of nursing care during home visits diagnosis that appears on Ny . D is the lack of knowledge related to the lack of information (effort eatment morning sickness ). Conclusion : The problem that occurs on the client nursing partially resolved so that interventions should still be continued.